Commanding heights [ the battle for the world economy - Barker, Greg; Cran, William; Stanislaw, Joseph; Stiers, David Ogden; Yergin, Daniel (WGBH Boston Video, 2003)
Explores our changing economic world: the clash between governments and the marketplace, the debate over the impact of globalization, and the forces shaping our future economy. Episode one considers the idea of government control in 20th century world economies, focusing on the economic theories presented by John Maynard Keynes and Freidrich Von Hayek. Episode two considers the failure of government-controlled economies in the 1980s. The focus is on how reform played out in Russia, the eastern bloc, Latin America, India, and other countries during this tumultuous time. Episode three tracks the global economy through the 1990s to the present. The focus is on the impact of free trade, global contagion, and the policies of the Clinton and Bush administrations